Contextual Antecedents of Psychological Well-Being in Physical Education - (:unkn) unknown (DERGIPARK AKAD, 2019)
The aim of the study was to examine contextual antecedents of psychological well-being in physical education classes. Data were collected from 431 high school students in two public high schools. Questionnaire pack consisted of the scales tapping students' perception of teacher's autonomy support, basic psychological needs satisfaction, intrinsic motivation, fear of negative evaluation, social appearance anxiety, subjective vitality and concentration. Path analysis supported a model in which autonomy support positively predicted students' psychological need satisfaction, which, in turn positively influenced students' intrinsic motivation. Intrinsic motivation positively predicted concentration and subjective vitality positively, fear of negative evaluation negatively. Bearing in mind that teacher's autonomy support in physical education can be considered as a tool to enhance adolescents' concentration and vitality while it can help to reduced adolescents' fear of negative evaluation and social appearance anxiety.
Keywords: autonomy support; motivation; basic psychological needs; psychological well-being; physical education; SELF-DETERMINATION THEORY; SOCIAL PHYSIQUE ANXIETY; SUBJECTIVE VITALITY; NEED SATISFACTION; AUTONOMY SUPPORT; MOTIVATIONAL PROFILES; HEALTH; OUTCOMES; MOTIVES; MODEL